Fiqh-legal foundations of personal and social health with emphasis on emerging diseases - Abdollah Jalili; Davood DadashNezhad Delshad; Morteza Barati (مطالعات فقه و حقوق اسلامی)
All members of the society have a responsibility to be cautious towards each other and must observe personal and social hygiene during the outbreak of infectious diseases so as not to cause its transmission and spread to others and other members of the society. Examining the jurisprudential and legal verdict of non-observance of hygiene against emerging infectious diseases and the guarantee and criminal responsibility of its transmitter is of great importance. Non-observance of personal and social health against various diseases, including emerging diseases, based on the rule of sanctity of self-harm, the rule of avoiding possible harm, the obligation to save life, the rule of negating harm, the rule of maintaining order, and the principle of caution is prohibited. be Also, the carrier of emerging infectious diseases is the guarantor based on the rule of wastage, the rule of attribution, the rule of respect, the rule of negation of harm, the rule of commitment to safety and the rule of commitment to the safety of conventional care, and the retribution of the carrier of the disease in case of death is received. The doer has been excluded because in intentional murder, supervision and the predominance of lethality are conditional verbs, if these two are the problem here. Also, based on some of the above-mentioned rules and international protocols and health regulations, any act or omission, carelessness and negligence that causes injury as a result of the occurrence and spread of various diseases and damage to the environment, including water, soil, air and sea pollution, is prohibited and guaranteed